2007
DOI: 10.1002/jcu.20393
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of gastrointestinal tract tumors during transabdominal sonographic examination: A clue to the diagnosis of gastrointestinal lymphoma

Abstract: Compressibility of the affected bowel is a useful clue in the diagnosis of GI lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Apart from that, Fujii et al demonstrated the compressibility of bowel lesion using ultrasound transducer to aid in differentiating gastrointestinal lymphoma from carcinoma. Compressibility was demonstrated in colorectal lymphoma which is absent in carcinoma [7].…”
Section: Discussionmentioning
confidence: 97%
“…Apart from that, Fujii et al demonstrated the compressibility of bowel lesion using ultrasound transducer to aid in differentiating gastrointestinal lymphoma from carcinoma. Compressibility was demonstrated in colorectal lymphoma which is absent in carcinoma [7].…”
Section: Discussionmentioning
confidence: 97%
“…H20084191) was injected into the antecubital vein at a dose of 1.5 mL/kg and a speed of 3.5 mL/s. The delayed contrast enhanced CT scan was performed at 26-180 s after the injection of the contrast [9][10][11][12]. The data of ROI were transmitted to the workstation for analysis and processing.…”
Section: Methodsmentioning
confidence: 99%
“…Various growth forms and involvement patterns can be differentiated on ultrasound [53,54]. The sonographic compressibility is more often retained than in the case of carcinomas [27,55].…”
Section: Non-hodgkin Lymphoma (Nhl)mentioning
confidence: 99%